Pengaruh Lingkungan Kerja, Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Pabrik Rokok Rejeki Barokah Prima Kabupaten Blitar. - Tegar Imannur Hakim; Khalikussabir Khalikussabir; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This research examines the influence of work environment, work discipline, and work motivation on employee performance at Rejeki Barokah Prima Cigarette Factory, Blitar Regency. A quantitative method with an explanatory approach was applied in this study. The research population included all employees working in the production and packing divisions, totaling 51 respondents, with sampling conducted using a saturated sampling method. Data were obtained through structured questionnaires and processed using multiple linear regression techniques. The findings indicate that work environment, work discipline, and work motivation simultaneously affect employee performance. On an individual basis, the work environment variable does not show a significant influence, whereas work discipline and work motivation demonstrate a positive and significant impact on employee performance. Keywords: Work Environment, Work Discipline, Work Motivation, Employee Performance